Cover Picture: Direct Correlation between Molecular Cross‐linking and Macroscopic Mechanical Properties for Green Solids of Deoxyribonucleic Acids (ChemNanoMat 11/2016). Issue 11 (11th October 2016) - Morimitsu, Yuma; Matsuno, Hisao; Ohta, Noboru; Sekiguchi, Hiroshi; Tanaka, Keiji
Abstract : Double‐stranded deoxyribonucleic acids (DNAs) were intermolecularly cross‐linked using 2, 5‐hexanedione based on reductive amination induced by 2‐picoline borane in aqueous phase. Atomic force microscopy revealed that while DNA chains near cross‐linking points were denatured to single‐strands, DNA chains not near cross‐linking points maintained B‐form double‐strands, which is the most typical conformation. A transparent, self‐supported, and mechanically toughened solid film was obtained from the cross‐linked DNAs by a simple solvent‐casting method. More information can be found in the Communication by H. Matsuno, K. Tanaka et al. onpage 1023 in Issue 11, 2016 (DOI:10.1002/cnma.201600222 ).